Optimal Capacity Configuration of Residential Solar-Hydrogen Coupling Energy System with Hydrogen Vehicle Load - Zhenlan DOU; Chunyan ZHANG; Huirong ZHAO; Yuqi YAO; Daogang PENG (Zhongguo dianli)
To address the impact of household hydrogen vehicles on residential energy system, an integrated residential energy system is designed with multiple types of energy storage devices including electric, thermal and hydrogen storage components coupled with photovoltaic/photothermal equipment. The mathematical model based on mixed integer linear programming theory is then proposed for system capacity configuration optimization. Firstly, with the high-efficiency photovoltaic and solar-thermal devices as the major energy production contributor, and the hydrogen energy as the major energy conversion and storage medium, the energy supply system architecture is designed to meet the residential electric, heat and hydrogen vehicle’s load requirements. Secondly, by setting the capacity of the equipment in the system as the optimization variable, and the minimization of annual investment cost of the system as the objective function, the reliability of energy supply and other factors as the constraints, the system optimal capacity configuration model is established. Finally, the system performance is evaluated in terms of the annual total investment saving rate and renewable energy utilization rate, which decreases by 42.21% and increases by 33.32% respectively after optimization. Meanwhile two different mobile load scenarios are constructed with exclusive electric vehicles and hydrogen energy vehicles respectively. Then the sensitivity analysis regarding the price of hydrogen energy equipment is carried out. It turns out that the residential energy supply system with hydrogen energy vehicle load will demonstrate more economic advantages if the hydrogen equipment price is reduced by more than 60%.